Effect of Chitosan Loading on the Morphological, Thermal, and Mechanical Properties of Diglycidyl Ether of Bisphenol A/Hexamethylenediamine Epoxy System. (30th October 2014) - Satheesh, B.; Tshai, K. Y.; Warrior, N. A.
Abstract : The effect of chitosan filled diglycidyl ether of bisphenol A (DGEBA) epoxy system were investigated using the thermal, mechanical, and morphological properties. The mixing ratio of resin/hardener was kept constant while the chitosan of 1.0, 2.5, 5.0, 7.5, and 10 weight percentage (wt%) was incorporated into the system. The thermal stability and the transition behaviour of the chitosan filled epoxy system were analysed through a differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR) while atomic force microscope (AFM) and scanning electron microscopy (SEM) were used to investigate the morphology. It was observed that the additive tends to agglomerate, with the formation of clear phase separation, when the chitosan content increases above 5 wt%. At lower chitosan loading (2.5 wt% and below), relatively uniform dispersion of the additive can be achieved. The thermal stability of the system increases with chitosan loading while the mechanical tensile strength is compromised.